Formation and characterization of self-patterned PZT film for applying to micro-mechanical detecting system - Ha, SM; Kim, WS; Park, HH; Kim, TS (TAYLOR & FRANCIS LTD, 2002)
One-layer self-patterned PZT film with 250 nm thickness was successfully fabricated using a photosensitive stock solution and UV-Irradiation process. Ethanol based-photosensitive stock solution having high molar concentration was prepared without any precipitation using diethanolamine (DEA) as stabilizer. A highly perpendicular edge shaped film was obtained through the self micro-patterning procedure. Especially the physical and electrical properties of self-patterned PZT films were compared with those of conventional PZT films. A highly densified microstructure with fine grains was obtained for both films but the self patterned one showed a highly (111) oriented microstructure. The remnant polarization of self-patterned film was slightly higher than that of conventionally processed film, however it showed a conventional and applicable ferroelectric properties.
Keywords: THIN-FILMS